EFL Teacher’s Oral Questioning: Are Her Questions and Strategies Effective? - Milawati, Milawati; Suryati, Nunung (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
Evidence is mounting that teacher question can assist EFL students in various purposes in teaching learning process. However, teacher’s lack of knowledge about questioning taxonomy could become a failure in leading students’ learning. This study investigates questioning strategies, the taxonomy of questions-type, and their application by teacher in advanced prose class, to scaffold students’ learning. Classroom observations, field notes and videotape recording, were employed to collect the data. Findings indicate that among four types of questioning strategies, redirecting was the most frequently used to initiate students’ responses and to probe more into students’ understanding. Other findings show that low-cognitive questions were common. Of those, knowledge-based questions were the most frequently used to confirm students’ understanding of the materials they learnt, but, the higher-level questions were rarely used. It was also found that teacher employed questioning strategies ineffectively to manage the class; insufficient time responded to a complex level of questions; the number of questions created confusion. Some changes to create effective classroom questioning and a stronger connection between the level of question and the questioning strategies are discussed.